2021
DOI: 10.3389/fpsyg.2021.672301
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Ethical Education, Physical Hatha Yoga, and Mantra Meditation on Well-Being and Stress in Healthy Participants—An Experimental Single-Case Study

Abstract: Traditionally, yoga is a multicomponent practice consisting of postures, breathing techniques, meditation, mantras, and ethics. To date, only a few studies have tried to dismantle the effects of each of these components and their combinations. To fill this gap, we examined the incremental effects of ethical education and physical Hatha yoga on mantra meditation using a single-case multiple-baseline design. This study was part of a project evaluating the new mind–body program Meditation-Based Lifestyle Modifica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 93 publications
7
23
0
Order By: Relevance
“…The program has been shown to be feasible and effective for depressive outpatients ( 33 , 34 ). In healthy individuals participating in the MBLM program, incremental and differential effects of practicing various components of the program could be seen, supporting the relevance of multilayered processes as described above ( 35 ).…”
Section: Introductionsupporting
confidence: 63%
“…The program has been shown to be feasible and effective for depressive outpatients ( 33 , 34 ). In healthy individuals participating in the MBLM program, incremental and differential effects of practicing various components of the program could be seen, supporting the relevance of multilayered processes as described above ( 35 ).…”
Section: Introductionsupporting
confidence: 63%
“…Preliminary clinical studies also suggest additional benefits on well‐being and prosocial behaviour (Andy Smith et al, 2011; Chen & Jordan, 2020). With respect to MBLM, the additive effects of the ethics modules on postural yoga and meditation has already been shown in healthy participants (Matko et al, 2021). In a feasibility study with depressive patients and in the qualitative evaluation for a subgroup of patients in the present study, the ethical component of MBLM was identified as a key factor in individual empowerment and appreciation of one's own strengths (Bringmann et al, 2021a; Bringmann et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…These results could be confirmed in a subsequent qualitative analysis, in which the high relevance of the ethical aspects for the participants and the associated reappraisal of their lives became apparent (Bringmann et al, 2021). Various components of MBLM also increased well‐being and reduced stress in psychologically healthy participants (Matko et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We randomised participants across these four conditions and across three baseline lengths (7, 14 or 21 days) using simple random sampling without replacement. A detailed breakdown of the study methods and the four treatments can be found in Matko et al (2021a).…”
Section: Methodsmentioning
confidence: 99%
“…MBM research so far has shown that people differ in their preferences regarding different psychological treatments (Williams et al, 2016), meditation techniques (Anderson & Farb, 2018;Burke, 2012), and practices of multi-component interventions that they use at home (Carmody et al, 2009). In addition, earlier studies found substantial interindividual variation in response to different contemplative treatments (Matko, Sedlmeier, et al, 2021a;May et al, 2014), and to psychotherapy (Saunders et al, 2019;Stulz et al, 2007). Several researchers pointed out that personality and other personality traits might tremendously influence the effects of meditation and yoga in this regard (Hölzel et al, 2011;Schmalzl et al, 2015;Tang & Braver, 2020).…”
Section: Introductionmentioning
confidence: 99%